Perancangan Media Pembelajaran Berbasis Mobile Matematika Materi Pengenalan Diagram Tingkat SD Kelas 1 - Rinal Dwi Septiawan; Lilik Sugiarto; Sri Widiyanti (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2023)
The graph of the average mathematics scores from 2021-2023 shows that the material for recognizing diagrams in 2023 received an average score of 60. Meanwhile, the KKM value for the material for recognizing diagrams is 62. So it can be concluded that the material for recognizing diagrams is below the KKM value. This research uses the method development of ADDIE (Analysis, Design, Development, Implementation, evaluation). framework used in instructional design to develop and implement effective learning programs. This method has 5 structured and flexible parts. At the quiz test stage of the application for grade 1 students at SDN 2 Gondangslamet. Get the results of the increase in value compared to the previous daily value. The design of interactive learning media regarding the introduction of diagrams uses Adobe Animate CC 2020 software for design, CorelDraw as an asset creation for the interactive media application for the introduction of diagrams. The research method uses ADDIE (analysis, design, development, implementation, evaluation), data collection techniques use observation, interviews, literature studies, questionnaires. b. The results of the questionnaire and tests, the results of the questionnaire showed a result of 86% and were included in the "Very Good" category in terms of design, text material and can make it easier for users to use the interactive learning media application for introducing diagrams. Then the assessment test shows an increase in scores based on interactive testing.